Efeito da umidade relativa sobre o desenvolvimento de micélio e conídios de microescleródios de metarhizium anisopliae em formulação peletizada - Catão, Alaine Maria Lopes (2016)
Metarhizium anisopliae has a worldwide repertation in microbial control due to its entomopathogenic characteristics, infecting a wide range of insects. High relative humidity is a key factor in the development of mycoses during extra-cuticular phases. In adverse conditions, M. anisopliae can produce resistance structures formed by hyphal aggregates. Upon high humidity these aggregates are capable of producing new conidia that can cause infection in the target host. However, the fungus not always finds suitable conditions of humidity to develop itself. To overcome constraints related to suboptimal humidities, formulations play a pivotal role, and formulated products containing additives, such as humectants, have a great potential to accomplish this goal. The objective of this study was to develop a pelletized formulation of hyphal aggregates of M. anisopliae IP 46 with or without addition of a humectant, and further evaluate the effect of relative humidity on conidia production of M. anisopliae in laboratory conditions. A screening with glycerin, propylene glycol and PEG 400 was performed to find out which humectant was best for water absorption. Hyphal aggregates were produced in specific semi-synthetic liquid medium. The biomass was filtered and pellets prepared with microcrystalline cellulose or vermiculite amended with or without glycerine. The relative humidity was assessed under controlled humidity gradient generated by aqueous solutions of NaCl. The water absorption rate with the glycerin appeared to be greater when compared to propylene glycol and PEG 400. Among the additives tested with glycerin, microcrystalline cellulose absorbed greater water content than the vermiculite, since the former has humectant properties increasing water absorption. The largest number of conidia, both for pellets with vermiculite and cellulose, was produced at 100% RH and the lowest production was achieved at 93 % RH. At humidities < 93% there was no conidia production up to 20 days, indicating a strong humidity effect in the fungal sporulation. An accumulation of water could be seen on pellets with 40% glycerin at humidity ≥ 91% and at 93% RH on pellets with glycerin 10%. This high water content could have been prevented the fungal growth. In pellets with addition of 10% glycerin, only pellets exposed to 91% RH produced conidia, both for cellulose pellets, and for vermiculite pellets.